SISTEM PENUNJANG KEPUTUSAN KESEHATAN UNTUK HIPERTENSI MENGGUNAKAN ALGORITMA C4.5 - Amalia, Hilda; Evicienna, Evicienna (LPPM Universitas Nusa Mandiri, 2013)
Hypertension is a cardiovascular disease that causes 4.5% of the global disease burden. Hypertension is a major risk factor for heart problems and can be said as the